(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the phenomenon of language contact and the linguistic nature of borrowed words from a theoretical perspective. The study highlights the role of internal and external sources in the development of a language, with particular emphasis on lexical borrowing that occurs as a result of interaction between languages. The theoretical foundations of language contact are analyzed based on the works of U.Weinreich and E.Haugen, focusing on the stages of borrowing, phonetic and grammatical adaptation, and the integration of borrowed words into the receiving language system. Using examples of words borrowed from Arabic and Persian-Tajik into the Uzbek language, the processes of phonetic adaptation and semantic expansion are illustrated. The findings demonstrate that borrowed words play a significant role in enriching the lexical system of the Uzbek language and represent a natural outcome of language contact.